The LBG Model and the Effctiveness of Socially Responsible Activities Measurement - Fijałkowska , Justyna (Studia Oeconomica Posnaniensia, 2016)
One of the primary factors affecting a company's credibility, and thus building its confidence in the assessment of its stakeholders, is the transparent communication of its activities. The aim of this article is to highlight the need for appropriate measurement and reporting of CSR effectiveness, as well as a description of the LBG model, which aims to support these challenges posed to accounting and management. This article presents the methodology of the LBG model, and shows its practical implementation in 67 CSR reports analyzed from the years 2015 and 2014. The research methods adopted in the article are a study of literature, source documents analysis and case studies, as well as the method of deduction. In the paper, the normative approach to accounting is applied.